POLA ASUH MAKAN (JENIS DAN FREKUENSI) “PROMPTING OR ENCOURAGEMENT TO EAT” BERKAITAN DENGAN KONSUMSI SAYUR PADA ANAK PRASEKOLAH BERUSIA 4 – 6 TAHUN - Elen Rambu Kahi Leba; Ronasari Mahaji Putri; Sulasmini (Akademi Keperawatan Hermina Manggala Husada, 2021)
There are many pre-school children who find it difficult to consume vegetables. Even though vegetables provide many benefits for the health of the child's body if consumed regularly. The eating habits in children cannot be separated from the role of parents, especially mothers, in encouraging children to consume vegetables or prompting or encouragement to eat. The purpose of this study was to determine the relationship between prompting or encouragement to eat eating patterns with vegetable consumption in preschool children aged 4-6 years. Correlative research design with cross sectional approach. The population is all mothers and preschool children aged 4-6 years in TK Dharma Wanita Persatuan Tlogomas, Lowokwaru District Malang City totaling 43 people, with a sample of 35 people using the Simple Random Sampling technique.The research instrument used a questionnaire in the form of a checklist and food frequency. Data analysis using Chi Square Test. The results showed that most of the mothers (60%) had a good